2021
DOI: 10.3389/fmed.2021.617891
|View full text |Cite
|
Sign up to set email alerts
|

Flash Glucose Monitoring to Assess Glycemic Control and Variability in Hemodialysis Patients: The GIOTTO Study

Abstract: Background: Flash glucose monitoring (FGM) is a technology with considerable differences compared to continuous glucose monitoring (CGM), but it has been scarcely studied in hemodialysis patients. Thus, we aimed assessing the performance of FGM in such patients by comparison to self-monitoring of blood glucose (SMBG). We will also focus on estimation of glycemic control and variability, and their relationships with parameters of glucose homeostasis.Methods: Thirty-one patients (20 with type 2 diabetes, T2DM, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“… Hissa et al [ 26 ] 2021, Prospective observational study 13 FreeStyle Libre 13 T2D /10 treated with insulin A 14-day FGM was performed in 13 diabetics on hemodialysis 15. Mambelli et al [ 12 ] 2021, Prospective observational study 31 FreeStyle Libre 20 T2D/without detailed information on the number treated with insulin/ 11 T1D A 14-day FGM was performed in 20 diabetics on hemodialysis and 11 individuals without diabetes on hemodialysis 16. Hayashi et al [ 21 ] 2021, Prospective observational study 98 System Gold Medtronic in 40 patients and Medtronic iPro2 in 58 98 T2D/65 treated with insulin, 20 treated with just oral hypoglycemic agents, 7 treated with just GLP-1A, 6 treated with diet A two-day CGM was performed in 98 diabetics on hemodialysis to record the glycemic profile of the dialysis day and the off-dialysis day 17.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… Hissa et al [ 26 ] 2021, Prospective observational study 13 FreeStyle Libre 13 T2D /10 treated with insulin A 14-day FGM was performed in 13 diabetics on hemodialysis 15. Mambelli et al [ 12 ] 2021, Prospective observational study 31 FreeStyle Libre 20 T2D/without detailed information on the number treated with insulin/ 11 T1D A 14-day FGM was performed in 20 diabetics on hemodialysis and 11 individuals without diabetes on hemodialysis 16. Hayashi et al [ 21 ] 2021, Prospective observational study 98 System Gold Medtronic in 40 patients and Medtronic iPro2 in 58 98 T2D/65 treated with insulin, 20 treated with just oral hypoglycemic agents, 7 treated with just GLP-1A, 6 treated with diet A two-day CGM was performed in 98 diabetics on hemodialysis to record the glycemic profile of the dialysis day and the off-dialysis day 17.…”
Section: Methodsmentioning
confidence: 99%
“…The quality and duration of the recording depend on the involvement in the testing process [ 8 , 9 ]. It has been proven that the latest models of continuous glucose monitoring and flash glucose monitoring sensors are characterized by high accuracy [ 10 12 ]. Moreover, continuous glucose monitoring is more promising in clinical practice than self-monitoring of blood glucose in terms of higher testing frequency and additional features such as assessment of glycemic trends, the use of alarms to detect abnormal glycemia (especially hypoglycemia), and the ability to track the blood glucose levels by partners, family members or healthcare professionals.…”
Section: Introductionmentioning
confidence: 99%
“…Mambelli et al. found very good accuracy of the Abbott Libre CGM in patients with type 2 diabetes on hemodialysis, with 97% of measurements in A+B regions of the Clarke error grid ( 95 ). In contrast, another study in patients with type 2 diabetes on hemodialysis by Yajima et al.…”
Section: Glucose Sensor Technologymentioning
confidence: 99%
“…Data regarding FGM and rtCGM accuracy in diabetic patients undergoing chronic HD are limited. The majority of the studies were conducted with FSL, the most frequently used CGM worldwide [46][47][48][49][50][51]. Small studies have demonstrated that the accuracy of FSL is lower in diabetic HD patients, especially during HD sessions as compared to SBGM/capillary blood glucose.…”
Section: What Is the Accuracy Of Cgm/fsl In Hd Diabetic Patients?mentioning
confidence: 99%